2020
DOI: 10.31362/patd.620783
|View full text |Cite
|
Sign up to set email alerts
|

Bir Tıp Fakültesi'nde internlerin ve araştırma görevlisi hekimlerin çocuk hakları konusundaki bilgi, tutum ve davranışları

Abstract: Özet Amaç: Bu çalışma ile bir tıp fakültesinde son sınıf öğrencilerinin ve araştırma görevlisi hekimlerin çocuk hakları konusunda bilgi, tutum ve davranışlarının değerlendirilmesi amaçlanmıştır. Gereç ve yöntem: Araştırmanın evrenini 323 kişi oluşturmaktadır. Örneklem seçilmeden evrenin tamamına ulaşılması hedeflenmiştir. Çalışma öncesinde etik kurul ve gerekli kurumsal izinler alınmıştır. Verilerin toplanmasında Çocuk Haklarına İlişkin Tutum Ölçeği'ni (ÇHTÖ) içeren anket formu kullanılmıştır. Ölçekten en az 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…However; similar to our re- sults, nursing and medical faculty students reported positive attitudes toward children's rights. 10,12,14 Also, the studies conducted with clinical nurses have shown that their positive attitudes continue following graduation. 1,5,8 In addition to this, the inclusion of the subject of children's rights in course content of midwifery and nursing students and their higher interaction with the children during their practical training have been suggested to contribute to their awareness of children's rights and to be a factor in developing a more positive attitude.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However; similar to our re- sults, nursing and medical faculty students reported positive attitudes toward children's rights. 10,12,14 Also, the studies conducted with clinical nurses have shown that their positive attitudes continue following graduation. 1,5,8 In addition to this, the inclusion of the subject of children's rights in course content of midwifery and nursing students and their higher interaction with the children during their practical training have been suggested to contribute to their awareness of children's rights and to be a factor in developing a more positive attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the studies conducted with students and graduate healthcare workers. 1,5,8,10,12,14,16,17 Karaman-Kepenekci indicated that the attitudes of the undergraduate students, who have taken a course on human rights and children's rights, were at a higher level. 15 Turan reported in their study with study-control groups that a statistically significant increase occurred in the attitude scores of the nursing students, who have taken a course on women and children's rights for 14 weeks, towards gender roles, violence against women and child abuse/neglect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Üniversite öğrencilerinin iklim değişikliği farkındalığı orta düzeyde tespit edilmiştir. Ülkemizde yapılan diğer çalışmalarda öğrencilerin küresel iklim değişikliği kavramını duydukları ancak konunun içeriğine ilişkin farkındalık düzeylerinin değişkenlik gösterdiği bulunmuştur (12)(13)(14) Öğrencilerin fakültelere göre küresel iklim değişikliği farkındalığı incelendiğinde toplam puanları açısından fark saptanmazken, sağlık alanında öğrencilerde doğal ve beşerî ortama etkiler ve enerji tüketimine ilişkin farkındalık daha yüksek iken, sağlık dışı alanlarda okuyanlarda küresel iklim değişikliğini ortaya çıkaran sebeplere yönelik farkındalık daha yüksek tespit edilmiştir. Pek çok çalışmada öğrencilerin çevreye yönelik eğitimlerini yetersiz olarak değerlendirdikleri gözlenmektedir (13,15,16,19,20).…”
Section: Tartışma Ve Sonuçunclassified